Reforming electricity reforms? Empirical evidence from Asian economies - Sen, A; Nepal, R; Jamasb, T (Oxford Institute for Energy Studies, 2016)
After more than two decades of attempts at electricity sector reform, there is a strong case for assessing empirical evidence on its outcomes, particularly for developing countries. Electricity reform programmes, implemented through the ‘standard’ or ‘textbook’ model, have their foundations in standard microeconomic theory and are based on the rationale that restructuring towards greater competition can lead to higher efficiency, maximise economic welfare, and transfer surplus to consumers. In practice, this has not always been the case, even in the OECD economies which pioneered the standard model. This paper investigates the outcomes of the standard model for developing countries, by applying instrumental variable regression techniques on an original and previously untested panel dataset covering 17 non-OECD developing Asian economies spanning 23 years. In contrast with the theoretical literature, our results show a tension between wider economic impacts and welfare impacts for consumers: namely, the variables that are associated with a positive effect on economic growth appear to be associated with a negative impact on welfare indicators. Our results show that institutional factors have influenced the outcomes, underscoring the point that the uniform application of the standard model without reference to the heterogeneity of the countries is unlikely to have resulted in originally intended outcomes. Our results call for a renewed thinking, or ‘reform’ of electricity reforms.